Inisiatif Pengembangan Desa Wisa Inisiatif Pengembangan Desa Wisata Wonodadi: Mengintegrasikan Children Adventure Tourism dan Kearifan Lokal untuk Pemberdayaan Masyarakat: Mengintegrasikan Children Adventure Tourism dan Kearifan Lokal untuk Pemberdayaan Masyarakat - Tiara Alfiani; Ardian Virgina Ariani; Putri Sahidah; Ipung Maulana; Nurratri Kurnia Sari (Universitas Veteran Bangun Nusantara, 2024)
The community service aims to develop Wonodadi Village as a children's adventure tourism destination that focuses on community empowerment and preservation of local wisdom. This program is implemented through three main stages, namely: 1) Observation and Analysis of Local Potential: Wonodadi Village has various natural, cultural, and economic potentials that have not been optimized, such as Goa Putri Kencana, Salam Village, bamboo crafts, honey bee farms, and gamelan art. 2) Development of Adventure Education Facilities: an educational tourism concept that combines local village potential. 3) Monitoring and Evaluation of activities. The evaluation results show an increase in public awareness of cultural preservation and management of local potential, the formation of village tourism managers, increased human resource capacity through MSME training, and optimization of cooperation between various parties. Overall, this community service creates a synergy between education, tourism, and entrepreneurship which is expected to increase tourist attractions, support cultural preservation, and improve the economy of the Wonodadi community.